0736 Daytime Activity Levels and Subsequent Changes in Cognitive Function in Older Men: The MrOS Study. (27th April 2018) - Li, J; Blackwell, T; McPhillips, M; Pack, A; Yaffe, K; Ancoli-Israel, S; Leng, Y; Gooneratne, N; Stone, K
Abstract: Introduction: Daytime physical activity (PA) and inactivity including napping, have been associated cognitive function in older adults. This study examined the associations between physical activity and subsequent change in cognition over six years in older men. Methods: A total of 1015 community dwelling men aged 67 and older, who were free of cognitive impairment at baseline, from the Osteoporotic Fractures in Men Study (MrOS), were included. Baseline PA was assessed using account/minute from wrist-worn actigraphs. Daytime inactivity measures include self-reported napping habits and actigraphically-derived periods of extreme inactivity (≥ 5mins of inactivity). The participants were categorized into four inactivity (or "nap") groups according to total daytime inactivity duration [none (≤5 minutes), short inactivity (6–30 minutes), moderate inactivity (31–90 minutes) and long inactivity (>90 minutes)]. Cognitive function was assessed using the Modified Mini-Mental State Examination (3MS). Change in cognition was analyzed continuously (Follow-up 3MS-Baseline 3MS) and dichotomously (≥5 points decline in 3MS). Results: Lower PA, longer periods of inactivity, and longer inactivity periods in the early evening (4pm-bedtime) were significantly associated with more rapid cognitive decline from baseline to follow-up, controlling for study site, age, race, education, body mass index, depression, history of hypertension, diabetes, self-reported health status, smoking, drinking, benzodiazepine use, antidepressant, and objective nocturnal sleep duration at baseline. People in the lowest quartile of PA experienced more cognitive decline than people in the other three quartiles (Q2: β=1.54, P=0.001; Q3: β=1.25, P=0.009; Q4: β=1.28, P=0.010). Those with long inactivity at baseline performed worse than those with moderate inactivity (β=-1.12, P=0.02). Clinically significant cognitive decline was observed in 22% of the sample at follow-up. Those with long inactivity periods had a 68% increased risk for cognitive decline at follow-up compared to the short inactivity group. Conclusion: Results suggest that lack of daytime activity, total daytime inactivity for more than 90 minutes, and early evening inactivity may be associated with undesirable changes in cognition/cognitive decline in older men. Support (If Any): K99NR016484, U01AR45580, U01AR45614, U01AR45632, U01AR45647, U01AR45654, U01AR45583, U01AG18197, U01AG027810, and UL1RR024140.